Chronic tonsillitis and its potential alternative treatment: Exploration of the antibacterial activity of ethanolic Mentha piperita leaf extract against bacterial isolates from patients - Munirwan, Puti G.; Setiani, Lily; Kurnia, Benny; Rahmawati, Novina; Ridwan, Azwar (Narra Sains Indonesia, 2026)
Chronic tonsillitis is commonly associated with persistent bacterial infection, predominantly involving Gram-positive organisms, and increasing antimicrobial resistance has encouraged exploration of alternative therapeutic agents derived from medicinal plants. Mint leaves (Mentha piperita) are known to contain bioactive compounds with potential antibacterial activity; however, their antibacterial efficacy against isolates specifically obtained from patients with chronic tonsillitis has not been clearly established. The aim of this study was to evaluate the antibacterial activity of ethanolic M. piperita leaf extract against bacterial isolates from patients with chronic tonsillitis. An experimental laboratory study was conducted using bacterial isolates from tonsillar core specimens. Antibacterial activity was assessed using the disk diffusion method at various extract concentrations, followed by determination of the minimum inhibitory concentration (MIC) by the microdilution method and the minimum bactericidal concentration (MBC) by subculture on plate count agar. Results showed that Gram-positive bacteria were the predominant isolates, with Staphylococcus aureus identified as the most frequent species, followed by Streptococcus agalactiae and Pseudomonas aeruginosa. The extract demonstrated greater inhibitory activity against Gram-positive bacteria, with the largest inhibition zone observed in Streptococcus agalactiae at 50% concentration (18.31 mm). In the microdilution assay, the lowest tested concentration (0.75%) inhibited bacterial growth in all tested species, and no colony growth was observed upon subculture, indicating bactericidal activity at this concentration. These findings suggest that ethanolic M. piperita leaf extract exhibits antibacterial activity, particularly against Gram-positive pathogens associated with chronic tonsillitis, and may represent a potential natural antimicrobial agent for further investigation.